Conserving Flora Biodiversity - Saribanon, Nonon; Amarullah, Amarullah; Ilmi , Fauziah; Effendi, Alvira Noer; Siregar, Zuhriansyah; Rafsanzani , Muhammad Firdaus (Universitas Nasional Jakarta, 2023)
The consideration of elderly welfare is paramount for achieving prosperity across all segments of society. To enhance the well-being of the elderly, the provision of green open spaces is imperative. These areas serve not only as places for relaxation and recreation but also foster a sense of togetherness and harmony in the relationship between humans and the environment. The creation of an Elderly Park aligns with these objectives, additionally serving as a locus for biodiversity conservation in rural settings. Conducted in Rahayu Village, Soko District, Tuban Regency, East Java, this research, executed in August-September 2023, employed field survey methods, encompassing interviews and non-transect vegetation analysis to catalog plant species. The primary goal of this investigation is to scrutinize plant species composition, ascertain biodiversity indices, compute estimated carbon biomass, and delineate the potential and conservation status of flora in Taman Lansia, Rahayu Village. The Elderly Park benefits 3,808 individuals from 1,298 families. The study revealed a plant composition of 61 species across 33 families, totaling 6,623 individuals. The flora biodiversity index (H') is 3.381 (High Category), and the flora species evenness index (E) is 0.8226 (High Category). The overall volume of flora carbon biomass measures 32.3741 m3, with a total biomass above the surface of 37.8453 kg. Of the identified plant species, 58 have potential applications in food and medicine, while 8 species possess LC, DD, and CD Conservation Status, necessitating preservation efforts within the Elderly Park.